VizieR Online Data Catalog: VI magnitudes of NGC 4535 stars (Spetsieri+, 2018) - Spetsieri, Z. T.; Bonanos, A. Z.; Kourniotis, M.; Yang, M.; Lianou, S.; Bellas-Velidis, I.; Gavras, P.; Hatzidimitriou, D.; Kopsacheili, M.; Moretti, M. I.; Nota, A.; Pouliasis, E.; et al. (VizieR Online Data Catalog, 2018)
We used archival observations of NGC 4535 taken with the HST WFPC2 as part of the HST Key Project. We used 13 epochs of F555W (equivalent to Johnson V) and 9 epochs of F814W (equivalent to Kron-Cousins I). The F555W data consisted in total of eight 3x1200 sec exposures and five 4x1300s exposures, while the F814W of nine 3x1300s exposures. (1 data file).
Keywords: Galaxies: nearby; Photometry: HST; Populations: stellar